The role of government and marketing strategy in increasing sales of MSMEs Liberty Ecoprint - Stivaniyanti Atmanegara; Feri Agus Romadhon; Indria Dwi Hapsari; Khusnul Mawazin (Jurnal Scientia, 2024)
The government provides strong support for the growth of MSMEs in Indonesia because of their vital role in encouraging people's economic activities. This support is reflected in the policies and regulations implemented, as well as the organization of events or exhibitions facilitated to involve MSME actors. The appropriate research method to reveal the role of the government and marketing strategy for the sale of Liberty Ecoprint MSMEs in Jember is a qualitative approach. The results of this study show that Liberty Ecoprint MSMEs can survive and have the potential to develop further through their innovations. Based on the results of the study, it was concluded that the role of the government and marketing strategies had a significant impact on the sales of Liberty Ecoprint MSMEs. In particular, promotion through social media and participation in exhibitions or events have proven effective in increasing sales as well as expanding the marketing reach for Liberty Ecoprint.